Sleep Positioning in Low Birth Weight Infants to Reduce Enteral Feeding Intolerance - Dyah Dwi Astuti; Yeni Rustina; Fajar Tri Waluyanti (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction: Enteral feeding intolerance is a common problem in low birth weight infants. This study aimed to analyze the effects of sleep positioning on low birth weight infants on the occurrence of enteral feeding intolerance. Methodology: This quasi experiment was applied on 20 low birth weight infants with a purposive sampling technique. The infants were grouped into control and intervention. Infants in the control group were given intervention with routine procedures; while those in the intervention group were performed prone sleep positioning after enteral feeding with the head of the bed elevated 30 degrees during the enteral feeding. Results: Independent t-test and Fisher’s Exact Test analysis showed that sleep positioning could decrease desaturation event (p value = 0.011), abdominal distension (p value = 0.017), and frequency of vomiting (p value = 0.035). Discussion: Nurses can make sleep positioning as standard operating procedures in low birth weight infants who have enteral feeding intolerance